Empowering the UMKM Sector in East Java through PROKESRA: A Study of Sales Growth and Labor Absorption - Asy’arie Fance Indriyanto; Riharjo Ikhsan Budi; Ardini Lilis; Nur Fadjrih Asyik (Journal of Applied Business and Technology, 2025)
The Micro, Small and Medium Enterprises (MSME) sector in Indonesia supports the national economy by contributing 61% of Indonesia's Gross Domestic Product. The MSME sector also absorbs 97% of the total national workforce. The aim of the research is to examine the effect of implementing the Prosperous Credit Program (PROKESRA) on sales growth and labor absorption. This research also examines the effect of MSME sales growth on labor absorption and examines the impact of credit terms on the effect of PROKESRA policy implementation on sales growth. The type of research is quantitative. The research population was 191 MSME actors accessing credit with interest subsidies in the Regency/City areas of East Java Province. The sample of PROKESRA credit recipients with interest subsidies was 191 MSMEs. Implementation of PROKESRA has a positive effect on labor absorption. This shows that 94% of PROKESRA has been implemented. Implementation of PROKESRA has no effect on sales growth, nor does sales growth have an effect on labor absorption. This shows that PROKESRA has not been able to support optimal sales growth, which is still at 48% (<50%). Furthermore, the credit period has an impact on the positive influence of the Implementation of PROKESRA on Labor Absorption. The impact of the credit term is categorized as a Pure Moderator.